THE FORMATION OF BIMETALLIC CONNECTION IN WELDER DEPOSITION UNDER LASER WELDING WITH THE FILLER WIRE FEED - A. P. Yelistratov (Литьë и металлургия)
The metallurgical and technological features of welding deposition in a robotic unit with a semiconductor laser are analyzed. The prospects of using beam with low energy density in the spot heating for applying metallic layers using filler wire are shown.